2019
DOI: 10.3390/ma12111797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polypropylene Fibre and Strain Rate on Dynamic Compressive Behaviour of Concrete

Abstract: This paper presents an experimental study on the dynamic compressive behaviour of polypropylene (PP) fibre reinforced concrete under various strain rates using split Hopkinson pressure bar (SHPB) equipment. The effects of PP fibre content and strain rate on the dynamic compressive stress-strain relationship and failure patterns were estimated. The results indicated that the addition of PP fibre enhanced the dynamic compressive properties of concrete mixtures although it resulted in a significant reduction in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Since Kolsky developed the SHPB technology for the dynamic mechanical test [ 26 ], the SHPB tests have been extensively applied to study the mechanical properties of various materials under strain rates ranging from 10 2 to 10 5 s −1 , such as metals, rocks, composite materials and solid propellant [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In this paper, an SHPB device was equipped to perform the impact loading experiment on the HTPB propellant.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Since Kolsky developed the SHPB technology for the dynamic mechanical test [ 26 ], the SHPB tests have been extensively applied to study the mechanical properties of various materials under strain rates ranging from 10 2 to 10 5 s −1 , such as metals, rocks, composite materials and solid propellant [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In this paper, an SHPB device was equipped to perform the impact loading experiment on the HTPB propellant.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Fibre reinforced concrete belongs to High Performance Concretes (HPC), which are typically used for strengthening linear horizontal members, for instance, beams [13,14]. The mechanical properties of fibre reinforced concretes are influenced by the type of used fibres, such as steel, glass, polypropylene of basalt [15][16][17]. The research [18] is focused on the mechanical properties and chloride resistance of chloride resistance of concrete reinforced with hybrid polypropylene and basalt fibres.…”
Section: Introductionmentioning
confidence: 99%
“… where is the static strength and is the dynamic maximal compression stress. When analyzing the dynamic properties of concrete by an SHPB device, the increase rate of the dynamic strength is often evaluated by the relationship between DIF and the logarithm of strain rate [ 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic mechanical properties of concrete materials have attracted much attention, and the Split Hopkinson Pressure Bar (SHPB) has been used as a common testing device to evaluate materials' impact performance. The strain rate sensitivity is proven to be one of the significant properties of concrete [28][29][30][31][32][33]. In recent years, some researchers found that severe environmental factors would seriously deteriorate the dynamic performance of concrete [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%